2017
DOI: 10.1080/13691058.2017.1371336
|View full text |Cite
|
Sign up to set email alerts
|

‘You just have to learn to keep moving on’: young women’s experiences with unplanned pregnancy in the Cook Islands

Abstract: The Cook Islands is one of several countries in the Pacific region that has high rates of teenage pregnancy and birth. While the social determinants of pregnancy and early motherhood are well established in the global context, little is known about how Cook Islands young women who become pregnant before age 20 make sense of their experiences. Drawing on individual interviews with a purposive sample of 10 young mothers, this paper examines the phenomenology of early pregnancy from their perspectives. Structural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…The eight articles [ 34 41 ] included for evaluation were studies conducted in PICTs with young people aged 10–24 years as main study participants and reported on young people’s responses to access to SRH information and services, thus meeting the inclusion criteria for this scoping review. Table 1 presents a summary of the studies’ characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The eight articles [ 34 41 ] included for evaluation were studies conducted in PICTs with young people aged 10–24 years as main study participants and reported on young people’s responses to access to SRH information and services, thus meeting the inclusion criteria for this scoping review. Table 1 presents a summary of the studies’ characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…All eight articles employed a qualitative design, and two [ 34 , 35 ] were from studies conducted in Papua New Guinea. Two articles [ 38 , 39 ] were from studies conducted in Fiji, two articles [ 36 , 37 ] were from one study conducted in Vanuatu, and the final two articles [ 40 , 41 ] were from one study conducted in the Cook Islands.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By assuming maternal identities, they redirect stigmatized constructions of their unplanned pregnancies as mistakes into moments of growth and transformation. In such contexts, shame is countered by emotions of happiness and pride which attend the motherhood role (White et al, 2018).…”
Section: Unplanned Pregnancies and Reproductive Agencymentioning
confidence: 99%